Relative Prevalence of Contact Allergens in North America in 2018. Issue 2 (March 2020) - Scheman, Andrew; Patel, Kevin R.; Roszko, Karolina; Severson, David; Brod, Bruce; Jacob, Sharon E.; Lloyd, Rita; Nedorost, Susan T.; Watsky, Kalman L.; West, Dennis P.
Abstract : Background: The American Contact Dermatitis Society Contact Allergen Management Program (CAMP) database was developed to provide patients with safe alternative products free of selected contact allergens. However, the CAMP database also records valuable information including the frequency of contact allergen searches for patients. Objectives: The aim of the study was to determine the relative prevalence of contact allergens in North America. Methods: Data from the CAMP database were analyzed from January 1, 2018, to January 1, 2019. The number of searches performed for each specific allergen served as a measure of the relative prevalence for each contact allergen. Results were then stratified by age, sex, atopic history, and patch screening tray used. Results: The 2018 CAMP data show that many of the prevalent allergens are not currently on any contact allergy screening series. These data strongly indicate that testing only to an 80-item screening series will not provide adequate care for many patients with contact allergy. The most prevalent contact allergens seen were fragrance mix, nickel, balsam of Peru, methylchloroisothiazolinone/methylisothiazolinone, and cobalt. Some important differences are seen when stratifying CAMP data by age, sex, atopic history, and patch screening tray used. Limitations: Possible sources of data error exist because of lack of uniformity of patch test practices. Conclusions: The CAMP database can be used to determine the relative prevalence of contact allergens, to help develop North American core screening patch test series, and to document the medical necessity of more comprehensive patch testing for patients with recalcitrant contact allergy. Capsule Summary: Previous studies have used databases from a limited number of practice sites to assess the relative prevalence of contact allergens. Data from the American Contact Dermatitis Society CAMP database were analyzed to determine the relative prevalence of contact allergens in North America during 2018. Data documenting the relative prevalence of contact allergens are critical in the selection of allergens for a North American core allergen series and to document the medical necessity for patch testing to additional allergens beyond the core series.